UTILIZATION OF COTTON ROVING WASTE IN SPINNING (Web of Technology: Multidimensional Research Journal, 2025)
The textile industry produces a considerable amount of waste during the spinning and roving stages. Cotton roving waste, often overlooked, represents a valuable secondary raw material that can be reintegrated into the production chain. This article explores the utilization of cotton waste in the case of roving, highlighting its recycling potential, environmental benefits, and economic implications. The study reviews recent approaches to reusing roving waste, its role in sustainable textile production, and practical strategies for integrating it into circular economy models. The results suggest that reprocessing roving waste not only reduces raw material consumption but also contributes to waste minimization and environmental sustainability.